A comparative study of the outcomes of fixation of fractures of distal femoral nailing versus plating - G. Singh, Thakur; Chhetri, Vaishali (International Journal of Research in Orthopaedics, 2025)
Background: Distal femur fractures have been historically very difficult to treat as they are often comminuted, unstable, more common in elderly or patients having multiple injuries. Hence, we conducted this study to assess the feasibility and the functional outcome of 30 cases of supracondylar fractures of femur, treated with locking compression plates and retrograde intramedullary supracondylar nails. Methods: All patients of distal femoral fractures were admitted and history was elicited to reveal the mechanism of the injury and the severity of the trauma, site of the incident, circumstances about which the injury occurred, premorbid medical history and preinjury functional status. Post-operatively patients were discharged with advice to continue physiotherapy as advised and to come for follow up after 3 weeks and later 3 months, 6 months,18 months and 24 months. Results: Among the 30 cases of supracondylar fracture fixed by supracondylar nail 14 had good scores and one was scored as excellent, whereas those fixed by locking compression plate 14 were scored as good and 1 case was scored as fair. There were no intances of surgical wound infections during the immediate postoperative period. Conclusions: From the observations and results of our study, it can be concluded that the supracondylar nail is more ideal when compared to the distal femoral locking compression plate as it has less operative time, less blood loss, more range of movement, less soft tissue stripping and faster radiological union when compared to the distal femoral locking compression plate.